Applying risk indices to assess and manage soil salinization and sodification in crop fields within a mediterranean hydro-agricultural area - Tomaz, Alexandra (2021)
SAICT-45-2017-02 POCI-01-0145-FEDER-007690 UIBD/00616/2020 PDR2020-101-030926